Design and planning of a 5G fixed wireless network - Silas Soo Tyokighir; Joseph M. Mom; Kingsley Eghonghon Ukhurebor; Gabriel A. Igwue (Institute of Advanced Engineering and Science, 2023)
This research explains how to design and plan fixed wireless access connections in an urban setting using 5th generation (5G) technology in a multi-user urban scenario. Although the antennas used had a high gain, the 28 GHz carrier frequency proved incompatible with the connections due to path loss. The additional loss due to foliage led to a drop in the receiver sensitivity to -84 dBm. The loss due to weather conditions resulted in lower received signal strength. The lower frequency of 3.5 GHz performed better and is recommended to establish successful communication over multi-kilometer distances. As a result, this study demonstrates how vulnerable high 5G carrier frequencies are to typical path loss impairments.